2006
DOI: 10.1136/jcp.2006.036970
|View full text |Cite
|
Sign up to set email alerts
|

Altered p-STAT3 (tyr705) expression is associated with histological grading and intratumour microvessel density in hepatocellular carcinoma

Abstract: Background: Constitutive activation of signal transducer and activator of transcription 3 at tyrosine residue 705 (p-STAT3 (tyr705)) has been associated with many types of human cancers. However, its potential roles and biological effects in hepatocellular carcinoma (HCC) are not well established. Aim: To explore whether an altered p-STAT3 (tyr705) expression is associated with angiogenesis or proliferation and thereby plays a part in HCC development. Methods: Paraffin-wax-embedded sections from 69 patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 38 publications
2
61
2
Order By: Relevance
“…Elevated STAT3 and p705 STAT3 expression in HCC tissue has also been reported [120]. Recent data also indicate an association of pSTAT3 with the histological grade of HCC tissue from 67 patients [201]. When anti-cancer small molecule S3I-201 was administered at a dose of 5 mg/kg every other day to xenografts of the human HCC cell line HUH-7, it was found that S3I-201 inhibited STAT3 tyrosine phosphorylation and tumor growth [6].…”
Section: Role Of Stat3 In Oncogenic Transformationmentioning
confidence: 98%
“…Elevated STAT3 and p705 STAT3 expression in HCC tissue has also been reported [120]. Recent data also indicate an association of pSTAT3 with the histological grade of HCC tissue from 67 patients [201]. When anti-cancer small molecule S3I-201 was administered at a dose of 5 mg/kg every other day to xenografts of the human HCC cell line HUH-7, it was found that S3I-201 inhibited STAT3 tyrosine phosphorylation and tumor growth [6].…”
Section: Role Of Stat3 In Oncogenic Transformationmentioning
confidence: 98%
“…STAT3 is regarded as a critical transcription activator for cell cycle or cell survival-related genes, and its phosphorylation has been linked to HCC tumor progression (42), angiogenesis (43) and tumorigenesis (44). Colomiere et al (45) have reported that activation of the JAK2/STAT3 pathway may result in EMT-associated phenotypes of ovarian cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Among the STAT family members, activated STAT3 plays a vital role in a diverse group of human cancers. Yang et al (9) detected pSTAT3 expression in 69 HCC and corresponding adjacent non-tumor parenchyma by immunohistochemistry, and found that 49.3% of HCC and 5.8% of non-tumorous tissues were positive for pSTAT3 nuclear staining. This observation differed quantitatively, but not qualitatively with our observation that pSTAT3-positive expression was observed in 54.3% of HCC and 31.8% of non-tumor tissues.…”
Section: Discussionmentioning
confidence: 99%